Negotiating Justice : Progressive Lawyering, Low-Income Clients, and the Quest for Social Change. - Shdaimah, Corey S. (Book collections on Project MUSE., 2009)
While many young people become lawyers for the big bucks, others are motivated by the pursuit of social justice, seeking to help people for whom legal services are financially, socially, or politically inaccessible. These progressive lawyers often bring a considerable degree of idealism to their work, and many leave the field due to insurmountable red tape and spiraling disillusionment. But what about those who stay? And what do their clients think? Negotiating Justice explores how progressive lawyers and their clients negotiate the dissonance between personal idealism and the realities of a s.